Analytical steady-state model based on Fourier integral transforms for cylindrical heat pipes under axisymetric conditions. (February 2022) - Blet, Nicolas; Maillet, Denis
Highlights: This paper proposes an original analytical modelling for cylindrical heat pipes in steady-state. The model is based on Fourier integral transforms and allows to take into account different types of boundary conditions at the interface liquid/vapour and outside. In simple cases, some intrinsic properties (impedances and transmittances) are introduced. The results are compared to some literature results for validation and are analysed. Abstract: A thermohydraulic analytical model of a capillary cylindrical heat pipe in steady-state is proposed in this article. It is based on an original representation by thermal quadrupoles to describe heat transfer in the wall and in the porous wick, via the use of Fourier integral transforms. Thanks to a validation from literature results, this model provides two-dimensional axisymetric thermal fields and one-dimensional pressure and velocity profiles of both liquid and vapour flows. Different developments and solutions are introduced according to the kind of boundary conditions at evaporator and at condenser, and with a more or less strong thermohydraulic coupling at the liquid/vapour interface. For the simple case with imposed uniform heat fluxes, intrinsic properties of the heat pipe are originally defined. The introduced model offers a generalisation of analytical models of standard heat pipe as a design or optimisation tool. Wider developments of analytical models for more complex three-dimensional geometries of heat pipe and in transient regime can be expected.